Diabetes Attenuates the Contribution of Endogenous Nitric Oxide but Not Nitroxyl to Endothelium Dependent Relaxation of Rat Carotid Arteries - Li, Jasmin Chendi; Velagic, Anida; Qin, Cheng Xue; Li, Mandy; Leo, Chen Huei; Kemp-Harper, Barbara K.; Ritchie, Rebecca H.; Woodman, Owen L. (Frontiers in Pharmacology, 2021)
Introduction. Endothelial dysfunction is a major risk factor for several of vascular complications of diabetes, including ischemic stroke. Nitroxyl (HNO), the one-electron reduced and protonated form of nitric oxide (NO•), is resistant to scavenging by superoxide, but roles of HNO in diabetes-mellitus associated endothelial dysfunction in the carotid-artery remains unknown. Aim. To assess how diabetes affects roles of endogenous-NO• and-HNO in endothelium-dependent relaxation in rat-isolated carotid-arteries. Methods. Male Sprague-Dawley rats were fed a high-fat-diet (HFD) for 2wks prior to administration of a low-dose streptozotocin (35mg/kg, i.p./day) for 2-days. The HFD was continued for further 12wks. Sham rats were fed standard-chow and administered with citrate-vehicle. After 14wks, rats were anesthetized and carotid-arteries collected to assess responses to endothelium-dependent vasodilator, acetylcholine (ACh) by myography. The combination of calcium-activated-potassium-channel-blockers, TRAM-34 (1μmol/L) and apamin (1μmol/L) was used to assess the contribution of endothelium-dependent-hyperpolarization to relaxation. The corresponding contribution of NOS-derived nitrogen-oxide species to relaxation was assessed using the combination of NO•-synthase-inhibitor, L-NAME (200μmol/L) and soluble-guanylate-cyclase inhibitor ODQ (10μmol/L). Lastly, L-cysteine (3mmol/L), a selective HNO-scavenger, and hydroxocobalamin (HXC; 100μmol/L), a NO•-scavenger, were used to distinguish between NO•-and HNO-mediated relaxation. Results. Diabetic rats exhibited significantly elevated blood glucose levels and retarded body-weight gain compared to sham rats. The sensitivity and maximal relaxation response to ACh was significantly impaired in carotid-arteries from diabetic rats, indicating endothelial dysfunction. The vasorelaxation evoked by ACh was abolished by L-NAME plus ODQ, but not affected by the apamin plus TRAM-34 combination, indicating that NOS-derived nitrogen-oxide species are the predominant endothelium-derived vasodilators in sham and diabetic rat carotid-arteries. The maximum relaxation to ACh was significantly decreased by L-cysteine in both sham and diabetic rats, whereas HXC attenuated ACh-induced relaxation only in sham rats, suggesting that diabetes impaired the contribution of NO•, whereas HNO-mediated vasorelaxation remained intact. Conclusion. Both NO• and HNO contribute to endothelium-dependent relaxation in carotid-arteries. In diabetes, NO•-mediated relaxation is impaired, whereas HNO-mediated relaxation was preserved. The potential for preserved HNO-activity under pathological conditions that are associated with oxidative-stress indicates that HNO-donors may represent a viable therapeutic approach to the treatment of vascular dysfunction.